Identifying challenges of change impact analysis for software projects - Osman Ali, Hassan (IEEE, 2012)
Project changes are difficult since the impacts of the changes are not readily known in advance. Changing customer needs and technology are driving factors influencing project evolution. Consequently, there is a need to assess the impact of these changes on existing software systems. For safety-critical system, the changes can even introduce hazards to bug down the system, particularly for larger systems, it quickly become difficult to comprehend what impact of requirement change might have on the overall system or parts of the system. Impact analysis is identifying the potential impact of disruption caused by a change to one or more components in the requirement on other components. The significant behind impact analysis is to identify requirement elements that may be affected by the change. However, this paper deals with impact analysis approach during project changes and identifies issues of impact analysis and where change impact analysis applied during software development projects.